Obstáculos didáticos na educação matemática: o conceito de números racionais no 6º ano do ensino fundamental. - Meier, Wander Mateus Branco (2012)
This work deals with the occurrence of the didactic obstacles in Mathematics' teaching, focusing on the apprenticeship of Rational Numbers, during the 6th grade of Elementary School. Its purpose consists on furnishing subsidies to the pedagogical practice of Mathematics, based on the historical-critical Pedagogy, which considers essential the educational work, which makes possible the appropriation of scientific knowledges in this area, and what, also, supports a conscious social proceeding. The first two chapters seek to support the camp research – which is cleared in third chapter - as a theoretical reference. The first chapter approaches the relationships between the school curriculum and society, considered fundamental to the analysis of the didactic action, because they influence it constantly. The second chapter presents the categories: whole, dialectical mediation, unit theory and practice, and contradiction, which are characterized as the basis of analysis of the didactic action, recorded by camp research. In the same chapter, an outline is made turned to the teaching of Mathematics, more specifically for the teaching of Rational Numbers, in order to fulfill the main objective of this work. The third chapter presents the methodology (subject, material and procedure) of the camp research and analysis of researched data. This is a camp research aimed at analyzing the pedagogical practice used by teachers of 6th grade, while introducing the concept of Rational Numbers, content that will constitute the basis for learning most of the other contents of the subsequent grades, in which, by its complexity, possible epistemological and didactic obstacles were searched. The camp research was conducted during the school year 2011, with two colleges of Public School System, in urban area of Cascavel. From the ensemble of collected data, with bases on the categories presented in first and second chapters, were extracted the elements for the analysis, without considering the chronology of events, and yes, their similarity, since the Annex 1: transcript of filmed lectures, presents wholly the same data. The camp research allowed to subsidize the educational work related to Rational Numbers, and its purpose was to emphasize about the obstacles originated from the didactic action itself, which can lead to epistemological obstacles. Finally, some considerations make the junction between the three chapters, linking the various relationships among didactic action, curriculum, historical-critical pedagogy, and society.